Utilization of Straw Resources May Affect the Speciation of Cd and Its Solubility in Cd-Contaminated Paddy Soil - Zuo, Wengang; Yi, Siqiang; Chen, Yasi; Huang, Gulin; Zhu, Xiaowen; Li, Yunlong; Gu, Chuanhui; Bai, Yanchao; Shan, Yuhua (Frontiers in Environmental Science, 2022)
Rice-wheat rotation has long been the most typical cropping system along the mid-lower reaches of the Yangtse River in China and full amount returning of wheat straw before rice season is widely practiced in the rotation system. However, massive incorporation of fresh wheat straw may activate Cd in soil solid phase and cause more labile Cd entering soil solution in Cd-contaminated soil during flooded rice season. An incubation experiment was conducted under flooded condition to investigate the solubility and speciation of Cd and its variation and driving factors with ongoing decomposition phase in simulated Cd-contaminated paddy soil treated with wheat straw addition. The results indicated that wheat straw addition enhanced Cd solubility, and soluble Cd concentration increased with ongoing decomposition phase. The observed significant positive correlation (r=0.648, p<0.01, n=77) between soluble Cd concentration and DOC content in soil leachate was gradually strengthened with ongoing decomposition. Wheat straw addition decreased the exchangeable fraction of Cd and increased residual fraction during the first 5 d decomposition. While the exchangeable Cd increased and the residual Cd decreased after 10 d decomposition. The exchangeable Cd increased and the residual Cd decreased gradually with ongoing decomposition. Correlation analysis showed that the exchangeable and residual fractions were sensitive to DOC content. Nitrogen fertilizer input further activated Cd by promoting wheat straw decomposition. In summary, wheat straw addition would activate Cd by increasing Cd solubility and promoting the translation from immobile fraction to labile fraction in Cd-contaminated paddy soil under flooded condition.